Circular RNA circ-MMP11 Contributes to Lapatinib Resistance of Breast Cancer Cells by Regulating the miR-153-3p/ANLN Axis - Wu, Xiaoli; Ren, Yi; Yao, Rong; Zhou, Leilei; Fan, Ruihua (Frontiers in Oncology, 2021)
Background: Chemo-resistance is a major obstacle to the treatment of breast cancer. Circular RNA (circRNA) circ-MMP11 has been reported to be promoting the progression of breast cancer. This study is designed to explore the role and mechanism of circ-MMP11 in lapatinib resistance in breast cancer. Methods: Circ-MMP11, microRNA-153-3p (miR-153-3p), and Anillin (ANLN) levels were detected by real-time quantitative polymerase chain reaction (RT-qPCR). Cell viability, number of colonies, apoptosis, migration, and invasion were detected by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT), colony formation, flow cytometry, and transwell assays, respectively. Exosomes were exerted and detected by differential centrifugation and a transmission electron microscope. The protein levels of CD63, CD9, and ANLN were assessed by western blot assay. The binding relationship between miR-153-3p and circ-MMP11 or ANLN was predicted by circinteractome or starbase, and then verified by a dual-luciferase reporter assay and RNA pull-down assay. The biological role of circ-MMP11 on breast cancer tumor growth and drug resistance was detected by the xenograft tumor model in vivo. Results: Circ-MMP11 and ANLN were highly expressed, and miR-153-3p was decreased in LR breast cancer tissues and cells. Circ-MMP11 could be transported by exosomes. Furthermore, circ-MMP11 knockdown promoted lapatinib sensitivity by repressing cell viability, colony number, migration, invasion, and boosting apoptosis in LR breast cancer cells. And circ-MMP11 deficiency improved the drug sensitivity of breast cancer in vivo. Mechanically, circ-MMP11 could regulate ANLN expression through sponging miR-153-3p. Conclusion: Circ-MMP11 could be transferred by exosomes in breast cancer cells. And circ-MMP11 functioned as a sponge of miR-153-3p to regulate ANLN expression, thereby promoting lapatinib resistance in breast cancer cells, providing therapeutic targets for the treatment of breast cancer.